Long Jump Ability: Analyze of Leg Explosive Power and Running Speed for Junior High School Students - Anggi Audina; Dewi Maya Sary; Awansyah Putra Karo Purba; Bebi Putra Sentosa Halawa (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. aims to determine the contribution of leg explosive power and running speed to long jump ability. Materials and methods. a research sample of 30 male students. Measurement of leg explosive power is determined by the ability to jump long without starting (standing broad jump). Running speed measurements are determined by running a sample distance of 30 meters. Measurement of long jump ability is determined by a sample of jumping as far as possible in the jumping. Results. The results showed that leg explosive power, leg length and running speed contributed to long jump ability (r > 0.05). The results show that leg explosive power and long jump ability contribute (r = 0.58). There was a contribution in the correlation test between running speed and long jump ability (r = 0.51). The results of the multiple correlation test of leg explosive power and running speed with long jump ability showed that there was a contribution (r=0.70 and r2 = 0.49) Conclusions. There is a contribution between leg explosive power, leg length and running speed to long jump ability. The influence of physical activity and regular and structured training also greatly influences a person's long jump ability